Specialized social assistance to families of victims of disappearance during the COVID-19 contingency - Escalera Silva, Luz Alejandra; Amador Corral, Sandra Rubí; Castellanos López, María Luisa (Cuadernos de Trabajo Social, 2021)
In Mexico, the situation of forced disappearance is critical; more than 73,000 families at the national level and more than 4,000 at the state level are affected by the situation they suffer when one of their relatives is missing. As a result of the health crisis caused by the global pandemic COVID-19, the vulnerability of families of disappeared persons has increased, although the epidemic is a generalized condition in this population, the effects are exacerbated by the conditions in which they live after the victimization. This document reports on the specialized attention that these families have received in the state of Nuevo León during this health crisis.